Usability of multibeam echosounder for wreck investigations using backscatter and water column data in shallow waters - Jai, Varun (The International Hydrographic Review, 2025)
With the increasing accuracy of survey equipment and the strict survey standards in modern times, the use of sophisticated equipment for hydrographic surveys has become standard practice. Multibeam echosounders (MBES) are an essential part of the inventory. This paper presents an analysis of two data sets collected using MBES and examines their applicability for wreck investigation. While the topic of MBES and wreck investigation is vast, this study is limited to two types of MBES in shallow waters. The analysis of the data sets indicates that MBES can effectively be used for wreck investigation in shallower waters when utilizing water column and backscatter data, adhering to the rigorous survey standards of today. This approach offers valuable insights for enhancing wreck investigation capabilities and meeting the demands of modern hydrographic surveys.